Sugar Quality Defect Identification Using Seven Tools and RCA: Identifikasi Cacat Kualitas Gula Menggunakan Tujuh Alat dan Analisis Penyebab Utama (RCA) - Moch Rio Firmansyah; Atikha Sidhi Cahyana (Indonesian Journal of Innovation Studies, 2026)
General Background: Quality control is essential in manufacturing industries to ensure product consistency and minimize defects. Specific Background: A sugar production company experienced significant product defects during the May–October production period, particularly in forms such as krikilan, refined sugar, and molasses. Knowledge Gap: Previous studies often apply quality control tools separately, with limited integration between statistical tools and root cause identification methods. Aims: This study aims to identify defect types, analyze root causes, and propose improvement strategies in sugar production processes. Results: The findings show that the highest defects occurred in krikilan with 1671 kwintal, followed by refined sugar and molasses. Analysis using seven tools revealed dominant defect patterns, while Root Cause Analysis identified five main contributing factors: machine, material, method, man, and environment. Novelty: The study integrates seven tools with RCA using the 5 Whys approach to provide a more structured and comprehensive defect analysis. Implications: The results suggest practical improvements including machine maintenance scheduling, stricter raw material inspection, and employee training to reduce defect rates and improve production efficiency. Keywords: Quality Control, Seven Tools, Root Cause Analysis, Sugar Production, Defect Analysis Key Findings Highlights Krikilan defect dominates total production issues across observed periods Integrated analysis reveals five primary sources of production failure Structured improvement actions focus on maintenance, supervision, and workforce capability